BENTUK KALIMAT, POSISI PROPOSISI, PRONOMINA, DAN NOMINALISASI DALAM RAGAM BAHASA POLITIK - Jupriono, D.; Lisna Amilia, Dinda; B.A.C. Paramita, Fransisca (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2022)
Focus of the research study is sentence form (active-passive, personal pronoun, propositional position, nominalization) on SBY speech as the research data. By linguistic approach of Fowler and van Dijk critics, the data analysis achieves the following findings: (1) Active sentence is chosen by SBY to tell a success, while passive sentence is used to express a failure. (2) Clausal proposition which tells a success is expressed by positioning at the front, and one which expresses a failure is faded at behind. (3) Pronoun kita is chosen to explain the negative and to avoid critics; the words saya and pemerintah are used to tell the positive, the pronouns mereka, siapa pun, or direct reference of collective one are applied to give warning or threat. (4) Nominalization is used by SBY to hide failure of conducting development program, so his image as the successful leader is spotless. Generally, it can be concluded that SBY makes use of sentence form as media of politic of self image as a successful leader and as a mask to cover failure and to avoid critics.